Legislation Functions of Members of the House of Representatives of the Republic of Indonesia in East Java Region I in the Implementation of Sidoarjo Regency Development Towards Good Local Governance: Fungsi Legislasi Anggota DPR RI Dapil I Jawa Timur dalam Implementasi Pembangunan Kabupaten Sidoarjo Menuju Good Local Governance - Muharram, Fajar; Agustina, Isna Fitria; Fitroni, Arif Senja (Procedia of Social Sciences and Humanities, 2022)
General elections (Pemilu) are the arena for the formation of representative democracy in a process of periodic leadership rotations. The general election conducted by the people is an essential part of the concept of a modern democratic state, besides being a form of embodiment of the people's sovereignty, which is guaranteed constitutionally. The elected council members in each Electoral District (Dapil) are expected to be able to assist the development program to the fullest. In other words, policy implementation must lead to good local governance. This research is categorized in descriptive qualitative research, with the implementation of interview and observation techniques in the data collection process. This research was conducted with the aim of finding out about legislation functions of the members of the DPR RI for the Regional Elections I of East Java in helping to realize good governance in Sidoarjo Regency.